EDUCATORS AND INFANTS: DIALOGUES OF THE CORPOREITY (Fiep Bulletin - online, 2014)
In this article, we wove reflections about the body, to corporeity, of two educators, since the infancy to its classroom.  We use a qualitative methodology, observations, interviews are structured, histories of life, photographs, filmings, groups of argument of the own pedagogical practice, theoretical reflections.  In this I study we resume significant points of the research:  The body of the infancy to the classroom that seeks to find roads for the formation of educators, creative and sensible educators.  The educators had different histories, roads and dreams.  It fitted them to same task: educate the infants for will be creative and active persons, and/or for will become repetitions of standards.  That it is a choice that each educator should do.  But, for that have conscience of such possibilities, is necessary that the educators, the educators know to itself, respect to its corporeity, reflect about the pedagogical practices.
Keywords: Body; educators; experiences; childlike education.